2019
DOI: 10.1002/iub.2071
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of long noncoding RNA GAS6‐AS2 promotes proliferation and inhibits apoptosis of melanoma cells via upregulating GAS6 expression

Abstract: Long noncoding RNAs (lncRNAs) are frequently aberrantly expressed and involved in many cancers, including melanoma. GAS6‐AS2 was a recently identified cancer‐related lncRNA. However, the expression, roles, and functional mechanisms of GAS6‐AS2 in melanoma remain unknown. In this study, we found that lncRNA GAS6‐AS2 is significantly elevated in melanoma tissues and cells. Elevated expression of GAS6‐AS2 is positively correlated with advanced stages and poor prognosis in melanoma. Functional assays demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Given that the levels of GAS6-AS2 in OS were distinctly up-regulated, we supposed GAS6-AS2 as a contributor in this tumor. Previous study by Wen et al showed that knockdown of GAS6-AS2 suppressed the proliferation and metastasis of melanoma cells, suggesting that GAS6-AS2 as a tumor promoter in this disease [16]. In this study, we also down-regulated the expressions of GAS6-AS2 in MG63 and 143B for the study of GAS6-AS2 function.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Given that the levels of GAS6-AS2 in OS were distinctly up-regulated, we supposed GAS6-AS2 as a contributor in this tumor. Previous study by Wen et al showed that knockdown of GAS6-AS2 suppressed the proliferation and metastasis of melanoma cells, suggesting that GAS6-AS2 as a tumor promoter in this disease [16]. In this study, we also down-regulated the expressions of GAS6-AS2 in MG63 and 143B for the study of GAS6-AS2 function.…”
Section: Discussionmentioning
confidence: 50%
“…Previous studies have confirmed that GAS6-AS2 was highly expressed in melanoma and bladder cancer tissues [15,16]. However, the potential mechanism involved in the upregulation of GAS6-AS2 in the above tumors has not been investigated.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, the alteration of LINC00261, C4A, and C4B following valproic acid treatment in motor neurons ( Yoshida et al, 2015 ), as well as the clustering of AC025280.2 with neuron-related genes ( Tenjin et al, 2020 ), suggest the possible role of these genes in neuron development. Additionally, while the expression and function of GAS6-DT in neurons and the brain remain unclear, there is evidence that GAS6-DT is involved in the upregulation of GAS6 gene expression in melanomas ( Wen et al, 2019 ). GAS6 is also a protein-coding hub gene associated with maturation (kME > 0.90), with roles in the central nervous system (CNS) ( Goudarzi et al, 2016 ), and highlighting a similar crosstalk between GAS6 and GAS6-DT can influence neuron development and maturation in the context of iPSC-derived neuron generation.…”
Section: Resultsmentioning
confidence: 99%
“…A number of lncRNAs have been shown to be differentially expressed in melanoma [29][30][31]. Several studies have also validated the relationship between dysregulated lncRNAs and melanoma pathogenesis, with these regulatory actions being mediated by multiple mechanistic interactions [32][33][34].…”
Section: Discussionmentioning
confidence: 99%